The Effect of Radiotherapy on Blood Components of Cervical Cancer Patients - Afina Yuliani Putri; Yan Wisnu Prajoko; Julian Dewantiningrum; Ch Nawangsih Prihharsanti (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Radiotherapy exposure is known to have a lethal effect on blood cells because hematopoietic cells are very sensitive to radiation exposure even at low doses. Cervical cancer with radiotherapy can have the effect of reducing blood cells. Blood cells that may experience the effects of radiotherapy include haemoglobin, leukocytes and platelets.Objective: Knowing the effects of radiotherapy towards blood components of cervical cancer patients.Methods: This study was an observational study with the type of study before and after design. Data collected from medical records as secondary data in the Radiotherapy Unit of Dr. Kariadi Semarang in 2019-2020 with a total of 128 cervical cancer patients undergoing 3D radiotherapy. The statistical test used the Saphiro Wilk data normality test and the result data analysis used the Paired T Test and the Wilcoxon test.Results: Hypothesis testing for Hb levels using the Paired T Test showed an insignificant value of p=0.749 and p=0.141. Hypothesis test for the number of leukocytes and platelets using the Wilcoxon test. Leukocytes received a significant value of p=0.000 and insignificant p=0.957. Platelets received a significant value of p=0.000 and p=0.000. Hb value decreased by -0.44, leukocytes by -3.5, and platelets by -84.34.Conclusion: There was an insignificant decrease in haemoglobin levels yet significant decrease in leukocyte and platelet counts in cervical cancer patients undergoing radiotherapy where the platelets experienced the most decrease compared to haemoglobin and leukocytes.